Time course of encoding and maintenance of stereoscopically induced size–distance scaling. Issue 10 (26th November 2022) - Guan, Wanyi; Li, Binglong; Qian, Jiehui
ABSTRACT: The mechanism of size constancy assures that an object is perceived to be constant in size despite that its retinal size varies with viewing distance. Conversely, an object can be perceived as illusorily larger if the perceived distance becomes greater, due to the size–distance scaling mechanism. The present study aimed at exploring how size–distance scaling is modulated by the encoding duration and how its memory is affected by the retention duration. In Experiment 1, we presented two stimuli simultaneously at two stereoscopic depth planes and manipulated the presentation duration, and found that the magnitude of the size scaling increased with presentation duration. In Experiment 2, we examined the maintenance of size–distance scaling when component stimulus was kept in working memory with variable delays. The results showed that the size scaling was reliably retrieved from working memory if there was no disparity manipulation on the to-be-memorized item, but it decreased with retention if a disparity was applied to the to-be-memorized item. The findings suggest that although the post-scaling size can be stored in working memory, the scaling mechanism may still be in effect when there were conflicts in the oculomotor cues and disparity cues that produces depth perception.